What is systematic theology? - Doran, Robert M., 1939- (Lonergan studies., 2005)
In his classic work Method in Theology, Bernard Lonergan left many questions unanswered in regard to his treatment of systematics. In What Is Systematic Theology? Robert M. Doran attempts to articulate and respond to these questions. Doran begins by accepting four emphases presented by Lonergan concerning systematics: first, that its principal function is the hypothetical and analogical understanding of the mysteries of faith; second, that it should begin with those mysteries of faith that have received dogmatic status; third, that it must proceed in the?order of teaching? rather than the?order of discovery?; and last, that it must be explanatory rather than merely descriptive. He then addresses questions that are raised by each of these emphases. What Is Systematic Theology? is the most thorough attempt undertaken to date to advance Lonergan?s program for systematics, fully in the spirit of his work but addressing issues that he left to others. Doran?s idea of a core set of meanings for systematics? or a?unified field structure?? is highly original, as is the integration of the systematic ideal and contemporary historical consciousness.